Vladimir Bibikhin as an Antipalamite - Leonkewich, Lucasz (Stasis, 2015)
Vladimir Bibikhin may be called a modernday antipalamite. He sharply rebukes Gregory Palamas’s theology of energy, which has had a profound influence on modern Orthodox theological thought. The Russian philosopher calls the Palamite doctrine a “theological failure,” asks why no one disputes Palamas today, and also why the God of Palamas, long ago divided in two, still remains divided into essence and energy. Emphasizing the Aristotelian concept of potential energy, he returns to the view that God is not divided, but rather exists as unmovable potential energy and as the Aristotelian Prime Mover.